Recent advancements in the design of micro/nanostructured superhydrophobic surfaces on magnesium alloys - Sihui Ouyang; Fengyi Wang; Jia She; Liying Qiao; Ao Fu; Xianhua Chen; Fusheng Pan (Journal of Magnesium and Alloys)
As one of the lightest engineering materials, magnesium (Mg) alloy possesses excellent mechanical performance, meeting the needs of versatile engineering fields and holding the potential to address cutting-edge issues in aerospace, electronics, biomedicine. The design of superhydrophobic (SHB) surfaces with micro and nanostructures can endow Mg alloys with multiple functionalities, such as self-cleaning, self-healing, antibacterial, and corrosion resistance. Over the past decade, researchers have drawn inspiration from nature to implement biomimetic design principles, resulting in the rapid development of micro/nanostructured SHB surfaces on Mg alloys, which hold great promise for biomedical applications. This review comprehensively introduces the biomimetic design principles of micro/nanostructured SHB surfaces on Mg alloys, discusses the challenges along with advantages and disadvantages of current preparation methods, and explores the future perspectives for preparing these SHB surfaces, providing strategies to enhance their performance in biomedical applications.